Exploring the Interpersonal Level of Music Performance Anxiety: Online Listener’s Accuracy in Detecting Performer Anxiety - Chang-Arana, Álvaro M.; Mavrolampados, Anastasios; Thompson, Marc R.; Pokki, Niklas; Sams, Mikko (Frontiers in Psychology, 2022)
Music performance anxiety (MPA) affects musicians at various stages of a performance, from its preparation until the aftermath of its delivery. Given the commonality and potentially grave consequences of MPA, it is understandable that much attention has been paid to the musician experiencing it. Consequently, we have learned a great deal about the intrapersonal level of MPA: how to measure it, treatments, experimental manipulations, and subjective experiences. However, MPA may also manifest at an interpersonal level by influencing how the performance is perceived. Yet, this has not yet been measured. This exploratory online study focuses on the listener’s perception of anxiety and compares it to the musician’s actual experienced anxiety. Forty-eight participants rated the amount of perceived anxiety of a pianist performing two pieces of contrasting difficulty in online-recital and practice conditions. Participants were presented with two stimulus modality conditions of the performance: audiovisual and audio-only. The listener’s perception of anxiety and its similarity to the musician’s experienced anxiety varies depending on variables such as the piece performed, the stimulus modality, as well as interactions between these variables and the listener’s musical background. We discuss the implications for performance and future research on the interpersonal level of MPA.